Investigation of mechanical properties and dynamic characteristics of OPEFB Fiber Composite - Zuhaimi Zuhaimi; Misran Misran; Indra Mawardi; Darmein Darmein; Nurlaili Nurlaili; Zaini AK; Hanif Hanif; Amir D (Politeknik Negeri Lhokseumawe, 2023)
Composite materials is increasingly experiencing an increa- sing trend, the manufacture of composites currently uses a lot of natural fiber reinforcement, Oil Palm Empty Fruit Bunches (OPEFB) fiber is a fiber that comes from oil palm empty fruit bunches waste that grows a lot in Indonesia and has the potential to be used as reinforcement in the manufacture of composites. With natural fiber reinforcement. The manufacture of composites in this study varied the fiber volume fraction by 5%, 15%, and 25%. Many previous studies on composite materials have focused on studying the physical and mechanical properties of composites. Even though damage to a structure or material is not only caused by static loads but also by dynamic loads. Vibration is a dynamic load experienced by material or structure, so it is necessary to determine the dynamic character of composite materials, one of the dynamic characteristics of materials is their natural frequency, the determination of the natural frequency in this study was carried out by using the finite element method in the ANSYS software. The results of the analysis in the form of tensile strength values and modulus of elasticity were obtained from tensile testing and dynamic characters in the form of natural frequencies and vibration modes were obtained from the analysis modal simulation process. From the results of the tensile test, it was found that the composite with a variation of 15% OPEFB fiber volume had the highest tensile strength and modulus of elasticity, as well as the results of the analysis modal simulation, a composite with 15% OPPEFB fiber, had the highest natural frequency value among the other two variations.